2023
DOI: 10.1002/jmv.28573
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of the stool DNA and RNA virome in Crohn's disease

Abstract: Pathogenesis of Crohn's disease (CD) relates to gut microbiome dysbiosis. However, less is known about the viral microbiome, consisting of bacteriophages and eukaryotic viruses, in CD. Here, we profiled the stool virome, viral functions, and viral-bacterial correlations that involved in CD pathogenesis. Metagenomics and metaviromics with novel viral identification and data analysis workflow were performed on stool of non-CD household controls, CD flare and remission patients.Both bacteriome and DNA/RNA virome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Notably, some functions related to viral replication and integration, phage lysis of bacteria host, virus-host biology, and bacterial susceptibility were decreased in T2D subjects, including ABC transporter, integrase core domain, DNA replication, transcription DNA-templated, translation, ribosome, beta-lactamase superfamily domain, glutamine metabolic process, and glutamine amidotransferase domain ( Figure 6 ). 20 , 21
Figure 6. Differential viral functions between (a) T2D subjects and healthy controls and (b) T2D-Ne subjects and healthy controls against GO and Pfam protein family databases.
…”
Section: Resultsmentioning
confidence: 99%
“…Notably, some functions related to viral replication and integration, phage lysis of bacteria host, virus-host biology, and bacterial susceptibility were decreased in T2D subjects, including ABC transporter, integrase core domain, DNA replication, transcription DNA-templated, translation, ribosome, beta-lactamase superfamily domain, glutamine metabolic process, and glutamine amidotransferase domain ( Figure 6 ). 20 , 21
Figure 6. Differential viral functions between (a) T2D subjects and healthy controls and (b) T2D-Ne subjects and healthy controls against GO and Pfam protein family databases.
…”
Section: Resultsmentioning
confidence: 99%
“… 29 , 30 Therefore, the higher relative abundance of lytic Faecalibacterium phages in cognitively impaired patients and correlation of these phages with poor cognitive testing could be due to their lytic action against Faecalibacterium . 31 On the other hand, Lactobacillus phages had a complicated relationship with bacteria and cognitive function longitudinally and cross-sectionally. 32 .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in anellovirus sequences has been observed in patients with IBD, strengthening the hypothesis that they may indirectly contribute to the progression of the disease [ 143 ]. In patients with CD, it was observed that TTV is related to inflammation in this disease, and relationships were found with complications and treatment approaches [ 144 ]. AVs are elevated in patients with IBD before initiation of therapeutic approaches.…”
Section: Immune System Diseasesmentioning
confidence: 99%